FORMATION OF CONTINUOUS ENVIRONMENTAL EDUCATION IN PRESCHOOLS AND SCHOOLS: INTERNATIONAL EXPERIENCE - Makhkamova Shakhrizoda Zukhriddin qizi; Usmonova Zukhrakhon Rakhmatovna; Alikarieva Durdona Mirmakhmudovna (Bright Mind Publishing, 2025)
This article analyzes international experience in continuous environmental education and upbringing and presents the results of practical research conducted in preschool institutions and schools in Tashkent. Observations, experimental activities, and surveys of teachers and parents were carried out. The results demonstrate that the inclusion of ecological games, project-based activities, and interactive educational resources contributes to the development of sustainable environmental attitudes in children.
Keywords: Environmental education, environmental upbringing, sustainable development, practice-oriented methods, digital technologies, environmental culture.